Analisis Studi Kelayakan Bisnis pada Seblak Teh Uun di Dusun Cambay Desa Jatibaru (Studi Kasus pada Aspek Pemasaran dan Aspek Manajemen) - Amalia, Fitria Fatihah; Manurung, Jessica Naomi; Savitri, Melany Indah; Munawaroh, Syarifah; Ken W, R.R Wening (BUDGETING : Journal of Business, Management and Accounting, 2024)
Indonesians, especially young people, are familiar with Bandung's specialties. Seblak is one of Indonesia's most popular dishes. Seblak has strong roots in the city of Bandung, West Java, but has now become an integral part of Indonesian cuisine that is favored by many people, especially among young people to the elderly. The purpose of this study is to assess the business feasibility of Seblak Teh Uun located in Cambay Hamlet, Jatibaru Village, East Cikarang Sub-district from a non-financial perspective. Non-financial variables, such as marketing aspects and management aspects. This research uses a qualitative data collection approach through interviews, observation, and documentation. Based on the results of non-financial findings such as marketing aspects and management aspects, Seblak Teh Uun in Cambay Hamlet, Jatibaru Village is feasible to develop. Seblak Teh Uun's business is considered feasible because in terms of quality ingredients. In addition, the marketing approach carried out through offline/online media that connects sellers and customers allows the business to continue. Keywords: Business Feasibility Study, Management Aspects, Marketing Aspects.